Tadpole of Hylodes fredi (Anura; Hylodidae), a frog endemic to an Atlantic Forest island (Ilha Grande, Rio de Janeiro State), Brazil - Laia, Rafael Camilo; Fatorelli, Pedro; Hatano, Fábio Haruki; Rocha, Carlos Frederico Duarte (Zootaxa, 2010)
The species of the genus Hylodes Fitzinger live on banks of small rivers and streams which run on rough terrain in eastern Brazil (Silva & Benmaman 2008). Hylodes fredi Canedo and Pombal 2007 is a recently described species endemic to Ilha Grande (Canedo and Pombal, 2007), an island covered by Atlantic Rainforest in the south of Rio de Janeiro State, Brazil. In this study, we present the description of the tadpole of H. fredi.